Accelerated crystallization of zeolites via hydroxyl free radicals - Feng, Guodong; Cheng, Peng; Yan, Wenfu; Boronat, Mercedes; Li, Xu; Su, Ji-Hu; Wang, Jianyu; Li, Yi; Corma, Avelino; Xu, Ruren; Yu, Jihong (Science (American Association for the Advancement of Science), 2016)
In the hydrothermal crystallization of zeolites from basic media, hydroxide ions (OH⁻) catalyze the depolymerization of the aluminosilicate gel by breaking the Si,AI–O–Si,AI bonds and catalyze the polymerization of the aluminosilicate anions around the hydrated cation species by remaking the Si,AI–O–Si,AI bonds. We report that hydroxyl free radicals (•OH) are involved in the zeolite crystallization under hydrothermal conditions. The crystallization processes of zeolites—such as Na–A, Na–X, NaZ–21, and silicalite-1—can be accelerated with hydroxyl free radicals generated by ultraviolet irradiation or Fenton's reagent.